Lions - Holmes, Kevin J. (Mankato, Minn. : Bridgestone Books, 1999)
An introduction to lions, covering their physical characteristics, habits, prey, and relationship to humans.
Includes bibliographical references (p. 23) and index.
530
Accelerated Reader AR
Keywords: Lions -- Juvenile literature; Lions